Cooperative learning model of snowball throwing to improve the activity and learning achievemens - Ari Arofi; Samsul Hadi; Samidjo Samidjo (Jurnal Taman Vokasi, 2018)
The aims of this research were to improve the activity and learning achievements of Cooling System subjects in class XI Light Vehicle Engineering (TKR) of Muhammadiyah 1 Imogiri Vocational School using the Cooperative Snowball Throwing type model. This research was a Classroom Action Research (CAR). The subject of this study was the tenth-grade students of Light Vehicle Engineering at Muhammadiyah 1 Imogiri Vocational School in the year 2017/2018, amounted to 29 students, while the object of this classroom action research was the application of the Snowball Throwing a type cooperative learning model. The data collection techniques used were observation and test. The instruments used were test sheets and observation sheets. The data analysis techniques used descriptive and quantitative analysis to determine the percentage of activity and learning were an achievement. The results of this research show that: (1) the application of the Snowball Throwing type cooperative learning model could improve students’ activity in the cooling system subjects. The result shows that the activeness score in the first cycle (48.8%) and increased in the second cycle became (68.2%), and (2) The application of the Snowball Throwing type cooperative learning model could improve the learning achievements of the Cooling System. The results show that the results of the pre-cycle test were 13.79%. Students who completed the first cycle of KKM were 13 students with a percentage of 44.9%. The test results in cycle II increased from cycle I. Students completed cycle II as many as 23 people with a percentage of 79.3%.